2006
DOI: 10.1002/adma.200600258
|View full text |Cite
|
Sign up to set email alerts
|

Evaporation‐Induced Self‐Assembly (EISA) at Its Limit: Ultrathin, Crystalline Patterns by Templating of Micellar Monolayers

Abstract: Patterning of surfaces at the nanoscale is important in many fields of application, e.g., for electronic devices, storage media, and as a starting base for the generation of more complex structures. To exemplify the latter subject, it has been shown that a periodic surface structure with periodicity of surface energy and topology allows for the alignment of liquid crystals [1] or the consecutive construction of channels or pillars being vertically aligned with respect to the substrate, [2] thus making the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
76
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(77 citation statements)
references
References 40 publications
1
76
0
Order By: Relevance
“…The construction of porous and hierarchically structured materials is accomplished by bridging together sol-gel chemistry, multiple templating, and advanced processing, namely Integrative Chemistry Strategy. The main chemical routes and strategies in this direction have been thoroughly described in several review articles [51][52][53].…”
Section: From Thin Films To Nanostructured Surfacesmentioning
confidence: 99%
“…The construction of porous and hierarchically structured materials is accomplished by bridging together sol-gel chemistry, multiple templating, and advanced processing, namely Integrative Chemistry Strategy. The main chemical routes and strategies in this direction have been thoroughly described in several review articles [51][52][53].…”
Section: From Thin Films To Nanostructured Surfacesmentioning
confidence: 99%
“…The rst case is the nanocasting process by using ordered mesoporous silicas or carbons as hard templates. Poly(ethylene-co-butylene)-b-poly(ethylene oxide) (PHB-b-PEO referred to also as "KLE") was rstly reported to synthesize highly crystalline cubic mesoporous TiO 2 lms through dip-coating by Smarsly and co-workers, but the whole mesostructure collapsed at 700 C. 31,32 Wiesner et al reported an effective method, called combined assembly by so and hard (CASH) chemistries, for highly crystalline mesoporous TiO 2 by using in situ generated sturdy, amorphous carbon derived from amphiphilic BCP polyisoprene-b-poly(ethylene oxide) (PI-b-PEO) as a rigid support to prevent the collapse of mesostructures during the crystallization. 23 The nanocasting method is an effective way to prepare mesoporous TiO 2 with crystalline frameworks.…”
Section: Introductionmentioning
confidence: 99%
“…[10] Control the formation of mesostructures in thin films using the EISA approach becomes increasingly difficult as the film thickness decreases. [11] However, a number of reports demonstrate the successful preparation of mesoporous structures in ultra-thin films. [11,12] The present work explores the possibility to fabricate and control well-defined nanostructures in ultra-thin films of functional hybrid materials based on amphiphilic diblock copolymers and metallic nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…[11] However, a number of reports demonstrate the successful preparation of mesoporous structures in ultra-thin films. [11,12] The present work explores the possibility to fabricate and control well-defined nanostructures in ultra-thin films of functional hybrid materials based on amphiphilic diblock copolymers and metallic nanoparticles. Additionally the block copolymer not only stabilizes the nanoparticles but allows to control the self-assembly.…”
Section: Introductionmentioning
confidence: 99%